Lobbying and Legislative Organization The Effect of the Vote of Confidence Procedure - Morten Bennedsen; Sven E. Feldmann (Copenhagen Business School (CBS), Department of Economics, 2002)
We analyze how the structure of organizational form of legislative institutions affects interest groups 'incentives to lobby.Lobbying is modelled the strategic provision of information by an interest group to a multi-person legislature.We show that the effectiveness of lobbying lies in changing the viable policy coalitions.We show in a multi-period policy framework that a distinguishing feature between the US Congress and European parliamentary systems – the vote of confidence procedure - can significantly change the incentives for interest group lobbying.
hdl:10398/7616
Keywords: A10; E10; E60; H00; 330; Organizational form; legislative institutions; Lobbying; Parliamentary systems; Politics; Interest groups